Making ‘MOOCs’: The Construction of a New Digital Higher Education within News Media Discourse - Bulfin, Scott; Pangrazio, Luciana; Selwyn, Neil (International Review of Research in Open and Distributed Learning, 2014)
One notable ‘disruptive’ impact of massive open online courses (MOOCs) has been an increased public discussion of online education. While much debate over the potential and challenges of MOOCs has taken place online confined largely to niche communities of practitioners and advocates, the rise of corporate ‘xMOOC’ ventures such as Coursera, edX and Udacity has prompted popular mass media interest at levels not seen with previous educational innovations. This article addresses this important societal outcome of the recent emergence of MOOCs as an educational form by examining the popular discursive construction of MOOCs over the past 24 months within mainstream news media sources in United States, Australia and the UK. In particular, we provide a critical account of what has been an important phase in the history of educational technology—detailing a period when popular discussion of MOOCs has far outweighed actual use/participation. We argue that a critical analysis of MOOC discourse throughout the past two years highlights broader societal struggles over education and digital technology—capturing a significant moment before these debates subside with the anticipated normalization and assimilation of MOOCs into educational practice. This analysis also sheds light on the influences underpinning how many people perceive MOOCs thereby leading to a better understanding of acceptance/adoption and rejection/resistance amongst various professional and popular publics.